Resisting the New Order: San Luis Potosí’s City Council Against the Mayor, 1787-1799 - Bernal Ruiz, Graciela (Anuario de Historia de América Latina, 2025)
This article analyzes the actions of resistance that influential groups in San Luis Potosí implemented against new politicians who introduced the Royal Mayoral Ordinance. They rebelled mainly through the city council, not only because its members were powerful individuals in the region, but because the Crown wanted to keep a close eye on its territory through the appointed mayors. Therefore, the opposition and resistance were carried out in confrontations against the main political character who was in charge of enforcing the Royal Ordinance in San Luis Potosí, Bruno Díaz Salcedo.